Land abandonment as a precursor of built-up development at the sprawling periphery of former socialist cities. (October 2015) - Grădinaru, Simona Raluca; Iojă, Cristian Ioan; Onose, Diana Andreea; Gavrilidis, Athanasios Alexandru; Pătru-Stupariu, Ileana; Kienast, Felix; Hersperger, Anna M.
Graphical abstract: Highlights: In former socialist cities, land abandonment is a precursor of built-up development. As an explanatory variable, land abandonment can increase prediction power of land use change models. Time lag between abandonment and transition to built-up areas can be used by authorities to reshape local public investments and priorities. Land abandonment in urban areas involves different processes and patterns compared to remote or rural areas. Abstract: In former socialist countries, as cities expanded they permeated into nearby agricultural areas. The periphery then became a mosaic of built-up and agricultural patches. Due to small sizes, inconvenient shapes and scattered locations, the parcels often became unprofitable for agricultural use, and were later abandoned and frequently transformed into built-up areas. Our paper aims to assess whether agricultural land abandonment can be considered a valid precursor of built-up development. The periphery of Bucharest was chosen as the study area, and analyzed over a period of 11 years (2002–2013) based on data sets derived from aerial images. Logistic regression models were used to test whether land abandonment was a significant explanatory variable of built-up development along with other socio-economic, land use, and urban planning variables. The results showed that land abandonment has the potential to be considered a precursor of built-up development. It acts within a cause and effect framework, being influenced by ongoing economic transformations, and changes in urban regulations. Its addition as an explanatory variable in a built-up prediction model significantly increased the prediction power, which makes it a useful variable in urban land use change scenarios. The type of observed abandonment at the periphery of urban areas follows a different pathway compared to land abandonment observed in remote or rural areas. Here, land abandonment is the result of anticipated higher profits through new economic opportunities and urbanization. Monitoring of abandoned land and urban sprawl could enable local authorities to evaluate the outcomes of planning policies and economic incentives.